The Data Analysis on Business Communication and Entrepreneurial Competency in Influencing Business Performance - Rida, Hardianti; Neneng, Hayati; Yudi Wahyudin, Suwandi; Deden, Abdul Wahab Sya’roni; Erwin, Yulianto (INTI International University, 2024)
MSMEs (Micro, Small, and Medium Enterprises) have great potential in the local economy and can be a solution to reduce the unemployment rate by absorbing more workers. One business sector that has received great attention is the culinary sector. MSMEs in the culinary segment have great potential to contribute to the local and national economy. The unsatisfactory performance of MSMEs in Indonesia is caused by a lack of quality human resources (HR) or a lack of expertise in entrepreneurship. This can be seen from the lack of progress in the knowledge of MSME players in aspects of management, organization, information and communication technology, marketing, and other skills that are essential in running a business. This research aims to obtain, know, study, and analyze the variables that will be mapped into the entrepreneurial model and their influence on business performance. The research method approach used is a Systematic Literature Review (SLR) which is carried out by identifying relevant research, assessing its quality, and scientifically summarizing the results of previous research. The results of research discussions found variables that would become entrepreneurial models in improving business performance. This research uses a human resource management approach, especially regarding factors that influence business performance. In this research, three variables were found to be used as research objects, namely two independent variables and one dependent variable. The novelty of the resulting research is creating an entrepreneurship model consisting of communication and entrepreneurial competence and their influence on business performance.